1993
DOI: 10.1051/forest:19930202
|View full text |Cite
|
Sign up to set email alerts
|

Modification de couleur du bois de chênes européens exposés à la lumière solaire

Abstract: (fig 22) to take into account the discoloration of wood under solar-type light exposure at the molecular level. In this paper, this model was extended to European species of oak (Quercus robur and petraea) with high levels of colored extractable substances and for which the color characteristics are a quality criterion. In addition to the observed and analyzed yellowing in Abies grandis wood, a color lightening corresponding to a lowered absorption over the spectral range (500-600 nm) (figs 2, 6) has been obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
1
5
0
2
Order By: Relevance
“…In the course of homolytic scission of intramolecular connections phenoxy free radicals arise. Most of them belong to the guaiacyl type [5]. The reactivity of these radicals is dependent of the quantity of oxygen in the surrounding [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of homolytic scission of intramolecular connections phenoxy free radicals arise. Most of them belong to the guaiacyl type [5]. The reactivity of these radicals is dependent of the quantity of oxygen in the surrounding [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring surface properties of grand fir samples impregnated by oak (Quercus pedunculata) extracts evidenced grand fir wood protection by these extracts. Comparison of photodegradation of grand fir and oak woods evidenced the involvement of extractives in the degradation process [16,17]. An ESR study showed that these phenolic coloured compounds not only act as filters, but also play a role in the radical processes involved in the photodegradation of wood: by radical transfer reactions, they deactivate radical oxygen species carrying oxidation process by producing stable phenoxyl (ΦO·) free radicals [10].…”
Section: Introductionmentioning
confidence: 99%
“…A negative correlation between wood lightness and sapwood width was found by Hoffmann (1987). Mazet et al (1993) showed significant differences between the sapwood and heartwood of sessile oak and European oak regarding their photochemical behavior. The abundant amount of extractives in heartwood, such as ellagitannins, explains such behavior (Scalbert et al 1987;Stich and Ebermann 1987).…”
Section: Introductionmentioning
confidence: 96%